2017
DOI: 10.5194/acp-2017-534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ozone Response to Emission Reductions in the Southeastern United States

Abstract: Abstract. Ozone (O3) formation in the southeastern U.S. is studied in relation to nitrogen oxide (NOx) emissions using longterm (1990s -2015)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 33 publications
6
11
0
Order By: Relevance
“…As a result, little previous work has assessed the OPE over multiple years at a particular rural site in the eastern United States. To the best of our knowledge, Hirsch et al (), Blanchard and Hidy (), and Henneman, Shen, et al () have done the only such studies. Hirsch et al () analyzed the seasonal variation of the observed OPE (∆O 3 /∆NO z ) at Harvard Forest, MA, from a 1990 to 1994 data record.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, little previous work has assessed the OPE over multiple years at a particular rural site in the eastern United States. To the best of our knowledge, Hirsch et al (), Blanchard and Hidy (), and Henneman, Shen, et al () have done the only such studies. Hirsch et al () analyzed the seasonal variation of the observed OPE (∆O 3 /∆NO z ) at Harvard Forest, MA, from a 1990 to 1994 data record.…”
Section: Introductionmentioning
confidence: 99%
“…After Hirsch et al () specified photochemically productive hours going from 11:00 to 17:00 EST, they found that the observed OPEs at Harvard Forest ranged from 4 to 8 ppb ppb −1 , with maximum OPE values occurring in either June or July of each year. In addition, part of Blanchard and Hidy () assessed observed OPEs (∆O 3 /∆NO z ) using available 14:00 local standard time measurements taken during June and July from 1997 to 2014 at four urban, one suburban, and three rural SouthEastern Aerosol Research and Characterization Network (SEARCH) sampling sites. Using a linear model, Blanchard and Hidy () determined that the OPEs at the two SEARCH sites most rural in character—Centreville, AL, and Yorkville, GA—increased from about 9 and 5 ppb ppb −1 , respectively, in 1997 to about 25 and 15 ppb ppb −1 , respectively, in 2014.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations